Stability or change? Social inequality at the transition from bachelor's to master's degree programmes in Germany. Empirical evidence from four graduate cohorts. (March 2023) - Reimer, David; Schwabe, Ulrike
For German higher education, the introduction of a two-cycle study structure resulted in a new transition stage after the completion of the bachelor's degree. In contrast to some other countries, this structural change was stretched over a relatively long period. At the same time, the number of students enrolled in higher education has increased substantially. Existing empirical evidence indicates that starting a master's degree programme is socially selective – in favour of students with tertiary qualified parents. Against this backdrop, we analyse how the level of social inequality at the new transition from the bachelor's to the master's level has developed over the course of the past two decades. Drawing on data from large-scale DZHW graduate surveys (graduate cohorts from the years 2005, 2009, 2013, 2017), we are able to replicate previous findings showing considerable social inequality at the transition to the master's level. However, this inequality could not be detected for the 2005 graduate cohort, the 'early adopters' . It seems that after an initial period of turmoil and uncertainty in the early stages of the implementation process, established patterns of inequality had re-emerged by the 2009 graduate cohort. We discuss the implications of our results for further research and policy-making.